El compliance program en la prevención del soborno en las empresas del sector construcción del distrito de Trujillo - Nolasco Ramírez, Erick Wilfredo (2020)
This research work was developed in light of the corruption scandals in Peru, in which several companies in the construction sector are being investigated. This is where the Compliance Program plays an important role in preventing crimes to which companies may be exposed. Therefore, this thesis proposes to determine whether the Compliance Program will prevent bribery in construction companies in the district of Trujillo. The research problem was: How will the Compliance program prevent bribery in the construction sector companies in the district of Trujillo? The hypothesis that was formulated was the following: The application of a Compliance Program will prevent bribery in companies of the construction sector in the district of Trujillo. According to the results achieved in tables 2, 3 and 4, it is determined that the Compliance Program will significantly prevent bribery in the construction sector companies; therefore, it will allow to fulfill the achievements and objectives set in this research. It is recommended to implement a Compliance Program in the companies of the construction sector for the prevention of bribery, under the approaches of the SGA (NTP ISO 37001:2017), considering what is indicated in Law 30424 and its regulations, and/or among other guides that are in accordance with the reality of the company.